Two cases of paragonimiasis westermani diagnosed after eosinophilic pleural effusion‐induced hydropneumothorax. Issue 3 (7th April 2016) - Yaguchi, Daizo; Ichikawa, Motoshi; Kobayashi, Daisuke; Inoue, Noriko; Shizu, Masato; Imai, Naoyuki
Abstract: Our hospital is located in the Tono region in the southeastern district of Gifu Prefecture in which there are forests and inhabitants who still hunt and eat game meat. Therefore, boar meat increases the risk of contracting paragonimiasis. We treated two patients who were infected by Paragonimus westermani after eating boar meat. They developed hydropneumothorax in association with eosinophilic pleural effusion. For patients who have pneumothorax with concomitant pleural effusion and eosinophilia in the pleural fluid analysis, it is necessary to take a detailed history, which includes flesh food consumption and travel to an endemic area, and to make a careful examination while taking into consideration parasitic infections such as paragonimiasis. Abstract : We describe 2 cases infected by Paragonimus westermani after eating boar meat who developed hydropneumothorax in association with eosinophilic pleural effusion. For such cases, it is necessary to take a detailed history, which includes flesh food consumption and travel to an endemic area, and to make a careful examination while taking into consideration parasitic infections such as paragonimiasis.